Choice paths in the Swedish upper secondary education - a critical discourse analysis of recent reforms - Lund, Stefan (Journal of education policy, 2008)
Decentralisation policy in Sweden emphasises school capitation allowance, the local upper secondary schools' decision-making and pupils' choices in contrast to previous bureaucratic governing. The aim of this article is to discuss how pupils' educational choice paths are a part of the different kinds of integration and differentiation processes within upper secondary education. By doing so, the intention is to make a theoretical contribution to the ongoing discussion in this research field. In the light of Habermas's theory of communicative action combined with Fairclough's critical discourse analysis, educational choice paths have been studied as a process within three educational practices in a local quasi-market in Sweden: (1) choice of upper secondary school, (2) choice of upper secondary programme, and (3) choice of courses and subjects within a programme. Some of the results demonstrate that pupils' choice paths can be vocation-oriented, career-oriented and consumption-oriented. It is argued that these different types of choice paths are related to a market discourse. Other results demonstrate that pupils' group-oriented, interest-oriented and tradition-oriented choice paths are built upon an active citizenship discourse, which is about creating meaning in terms of seeking knowledge and establishing social relations in upper secondary education. The analysis of these two paramount discourses indicates that pupils' integration and differentiation processes are ambiguous.